Research Paper: Using Subpubic Angle in Sex Determination and Stature Estimation: An Anthropometric Study on Iranian Adult Population - Akhlaghi, Mitra; Bakhttavar, Khadijeh; Mokhtari, Tahmineh; Mehdizadeh, Farzaneh; Allahyar Parsa, Vida; Vasheghani Farahani, Masoumeh; Vasheghani Farahani, Maryam; Sadeghian, Mohammad Hossein (International Journal of Medical Toxicology and Forensic Medicine, 2017)
Background: Pelvic bone has important sex determining features. However, anthropometric reference values vary by study population. This study aimed to determine the accuracy of subpubic angle for sex determination and height estimation in Iranian adults. Methods: In this study, the subpubic angle in the digital pelvic radiographs of 325 Iranian adults (199 males and 126 females) and their standing heights were measured. Then, the relation of subpubic angle with sex and stature was evaluated. Results: The mean(SD) subpubic angle of the studied population was 116.3 (23.7) degrees. Subpubic angle was significantly wider (P<0.001) in females [140.5(14.3) degrees] compared to males [101.0(13.3) degrees]. Moreover, we observed a significant decrease (P<0.001) in females’ subpubic angle with an increase in age. A significant reverse correlation (P<0.01) was also observed between the subpubic angle and height (r=0.416). Conclusion: This study showed that the mean subpubic angle in Iranian adults is different from the average in other populations. Our reference values can be used in forensic identification.